2005
DOI: 10.1089/end.2005.19.11
|View full text |Cite
|
Sign up to set email alerts
|

Shockwave Therapy as First-Line Treatment for Peyronie's Disease: A Prospective Study

Abstract: Our results support SWT as an effective and safe first-line treatment for Peyronie's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 15 publications
2
11
0
Order By: Relevance
“…Most of these ED patients had an organic etiology, such as a vascular lesion [7,8], a nerve injury [9], or a lesion of the cavernous body of E U R O P E A N U R O L O G Y X X X ( 2 0 1 6 ) X X X -X X X [10][11][12][13]. One study focused on ED patients with chronic pelvic pain [14].…”
Section: Evidence Synthesismentioning
confidence: 99%
“…Most of these ED patients had an organic etiology, such as a vascular lesion [7,8], a nerve injury [9], or a lesion of the cavernous body of E U R O P E A N U R O L O G Y X X X ( 2 0 1 6 ) X X X -X X X [10][11][12][13]. One study focused on ED patients with chronic pelvic pain [14].…”
Section: Evidence Synthesismentioning
confidence: 99%
“…Although a large-scale randomized clinical trial comparing treatments for Peyronie's disease is not yet available, several studies have reported that extracorporeal shock wave therapy (ESWT) is a useful alternative to relieve painful erections [5][6][7][8][9][10][11][12][13][14][15]. Almost all the abovementioned studies considered that ESWT is a non-invasive modality and appears to be a safe and effective procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Although penile extracorporeal shock wave therapy (ESWT) has been proposed as a nonsurgical PD treatment and a few reports demonstrated a beneficial effect [57,58], most studies did not observe any significant change in penile curvature [ …”
Section: Extracorporeal Shock Wave Therapymentioning
confidence: 99%